Respuesta :
i am assuming when you write 27x5 u mean "27 times x to the power of 5".
therefore, your answer is 9x3-11x2-7x
therefore, your answer is 9x3-11x2-7x
Answer:
[tex]\frac{f(x)}{g(x)}=(9x^3-11x-7x[/tex]
Step-by-step explanation:
Given function [tex]f(x) = 27x^5-33x^4-21x^3[/tex] and [tex]g(x)=3x^2[/tex]
We have to find f of x over g of x that is [tex]\frac{f(x)}{g(x)}[/tex]
Consider ,
[tex]f(x) = 27x^5-33x^4-21x^3[/tex] and [tex]g(x)=3x^2[/tex]
To find [tex]\frac{f(x)}{g(x)}[/tex]
Substitute the values for functions, we get,
[tex]\frac{f(x)}{g(x)}=\frac{27x^5-33x^4-21x^3}{3x^2}[/tex]
Taking [tex]3x^2[/tex] common from numerator, we get,
[tex]\frac{f(x)}{g(x)}=\frac{3x^2(9x^3-11x-7x)}{3x^2}[/tex]
Thus, [tex]3x^2[/tex] gets cancel, we get,
[tex]\frac{f(x)}{g(x)}=9x^3-11x-7x[/tex]
Thus, value of function f of x over g of x is [tex]9x^3-11x-7x[/tex]